Studies on the Effect of Crop Geometry and Nutrient Management on Productivity and Economics of Baby Corn and Cowpea (Fodder) Intercropping System - Barik, A. K.; Karmakar, M.; Ghorai, S. K. (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted during kharif season of 2012 and 2013 at agricultural research farm, Palli Siksha Bhavana (Institute of Agriculture), Visva-Bharati, Sriniketan, West Bengal to study the effect of crop geometry and nutrient management on productivity and economics of baby corn and cowpea (fodder) intercropping system. The experiment was laid out in randomized block design having twelve treatments with each treatment replicated thrice. Higher numbers, length, girth, fresh and dry weight of baby cob as well as baby corn were recorded in various intercropping systems viz. 2:1, 2:2 row ratios with 100% NPK of base crop+75% PK of intercrop when compared with sole crop of baby corn. Higher number of corns ha-1, baby corn yield and green fodder yield of baby corn and cowpea were found in sole crop of baby corn and cowpea, respectively. This was significantly higher than various intercropping systems. Total green fodder yield in different intercropping systems was higher than sole cowpea but lower than sole crop of baby corn. The treatment having 3:1 row ratio of baby corn and cowpea with 100% NPK of base crop+75% PK of intercrop exhibited significantly higher total dry fodder yield over sole crop of cowpea and at par with sole crop of baby corn. The highest gross return, net return and return rupee-1 investment was achieved in sole crop of baby corn which was significantly higher than all other intercropping combinations as well as sole crop of Cowpea.